Consensus on the treatment of hidradenitis suppurativa - Brazilian Society of Dermatology - Renata Ferreira Magalhães; Maria Cecília Rivitti-Machado; Gleison Vieira Duarte; Roberto Souto; Daniel Holthausen Nunes; Mario Chaves; Sérgio Henrique Hirata; Andrea Machado Coelho Ramos (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Hidradenitis suppurativa is a chronic immune mediated disease of universal distribution that causes great damage to the quality of life of the affected individual, whose prevalence is estimated at 0.41% in the Brazilian population. The objective of this work was update on physiopathogenesis, diagnosis and classification of hidradenitis suppurativa and to establish therapeutic recommendations in the Brazilian reality. It was organized as a work group composed of eight dermatologists from several institutions of the country with experience in the treatment of hidradenitis suppurativa and carried out review on the topic. Recommendations were elaborated and voted by modified Delphi system and statistical analysis of the results was performed. The Brazilian consensus on the clinical approach of hidradenitis suppurativa had the support of the Brazilian Society of Dermatology.